Establishing circularity: development and validation of the circular work value scale (CWVS) - Schneider, Jannick; Striebing, Clemens; Hochfeld, Katharina; Lorenz, Timo (Frontiers in Psychology, 2024)
Objectives Addressing the lack of German-language instruments, this study aims to develop a questionnaire that enables the measurement of work values. According to the theory of basic human values (Schwartz, 1992), a culturally fitting questionnaire is validated by covering constructs in the four broader dimensions of Social, Prestige, Intrinsic, and Extrinsic work values. Convergent, discriminant and incremental congruent validity are assessed. Method Data were collected in a cross-sectional online-based panel survey. Individuals working more than 20 h per week were included (N = 1,049). Using a genetic algorithm, an economical and valid questionnaire was designed to assess work values. Results The 11 work values are measurable with three items each. They provide a good fit to the data with support for strict measurement invariance. The empirical associations to estimate construct validity overall reflect expected relations to social and individualistic work motives, neuroticism, environmental awareness, and basic values. Furthermore, congruent incremental validity is supported with relations to value congruence of the person–organization fit, and multidimensional scaling supports the assumed theoretical circularity of the work values. Implications This study developed a questionnaire that enables a theory-based valid measurement of work values. The questionnaire allows practitioners to economically collect information about the value structure of employees or applicants. Future research should consider the development of work values over time and investigate whether more distinctive constructs provide a better fit in the nomological network.